+0  
 
0
132
3
avatar

I have no idea how to do this. Please help!

 Sep 6, 2018
 #1
avatar+98197 
+1

a. 4f(x)  = 4 ( l 4 - 3x^2 l )   =   4 l 4 - 3x^2 l

 

b. 2g (x - 3)  =   2 [ 3(4)x-3 ]  = 6(4)x-3

 

c. h(x + 3) + 4   =    log3 ( [x + 3] - 5) + 4   = log3 (x - 2) + 4

 

 

cool cool cool

 Sep 6, 2018
 #2
avatar
+1

Hi, thanks for answering! Just one quick question, for part A, what type of transformation is it?

Guest Sep 6, 2018
 #3
avatar+98197 
+1

"A" will  produce  vertical "stretching " by a factor  of 4

 

 

 

cool cool cool

CPhill  Sep 6, 2018

36 Online Users

avatar
avatar
avatar